2019
DOI: 10.1016/j.amjcard.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Elevated Resting Heart Rate in Mid-Life to Cognitive Decline Over 20 Years (from the Atherosclerosis Risk in Communities [ARIC] Study)

Abstract: Resting heart rate (RHR) is independently associated with cardiovascular disease (CVD) risk. We determined whether RHR, measured in mid-life, is also associated with cognitive decline. We studied 13,720 middle-aged white and black ARIC participants without a prior history of stroke or atrial fibrillation. RHR was obtained from a 12-lead resting electrocardiogram at the baseline visit (1990)(1991)(1992) and categorized into groups as <60 (reference), 60-69, 70-79 and ≥80 bpm. Cognitive scores were obtained at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 22 publications
(23 reference statements)
0
33
0
Order By: Relevance
“…18 According to studies evaluating resting HR and target organ damage, elevated resting HR is associated with higher frequencies of albuminuria, 16 progression to chronic kidney disease, 15 accelerated arterial stiffness, 14,25 and cognitive decline. 26,27 On the basis of currently available evidence, it is plausible that subjects with an elevated resting HR would be more likely to develop ECG-LVH.…”
Section: Discussionmentioning
confidence: 99%
“…18 According to studies evaluating resting HR and target organ damage, elevated resting HR is associated with higher frequencies of albuminuria, 16 progression to chronic kidney disease, 15 accelerated arterial stiffness, 14,25 and cognitive decline. 26,27 On the basis of currently available evidence, it is plausible that subjects with an elevated resting HR would be more likely to develop ECG-LVH.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite robust adjustment, residual confounding may still explain associations see with incident dementia. Finally, our method of dementia ascertainment may be more comprehensive than other studies because in addition to review of medical and death certificate records, an in-person neuropsychological assessment, informant interview, and expert review were all used to adjudicate the cases of dementia [3135].…”
Section: Discussionmentioning
confidence: 99%
“…Incident dementia cases in ARIC were adjudicated by an expert dementia classification committee comprised of eight clinicians including four physicians and four neuropsychologists [31]. Dementia was ascertained using a pre-determined algorithm, incorporating data from the cognitive tests performed at ARIC visits 2, 4, and 5, the full neuropsychological assessment performed at visit 5, participant interviews, informant (family member) interviews, and also hospital discharge codes and diagnostic codes from death certificates, as has been previously described in ARIC [3135]. Each dementia case was adjudicated by a physician (either a geriatrician or neurologist) and a neuropsychologist, and in cases of disagreement a third clinician confirmed the diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…RHR is a vital sign that is routinely measured at most clinical encounters, as well as self-monitored by individuals using fitness trackers and mobile devices. Prior studies have demonstrated that elevated RHR is associated with an increased risk of CVD, all-cause mortality,6–10 valvular heart disease25 26 and cognitive decline 24. However, there is little literature available on its role with VTE.…”
Section: Discussionmentioning
confidence: 99%
“…We used two samples t-test, Mann-Whitney test or X 2 test to describe differences between groups as appropriate. We used multivariable-adjusted Cox proportional hazards regression models to determine the HRs and 95% CIs of incident VTE by RHR groups categorised by previously established cut points (<60, 60–69, 70–79 and ≥80 bpm) 10 24 25. We tested for trends across RHR categories by using an ordinal variable for each RHR category and modelling this as a continuous variable for association with VTE.…”
Section: Methodsmentioning
confidence: 99%